L’esclusione sociale dei rom: una storia, tra oblio e violenza istituzionale - Chiavetta, Martina (Studi Politici, 2023)
Through a historical-social approach, the essay aims to provide a comprehensive overview of the historical events and social processes that have led to increasingly radicalized phenomena of social exclusion of Roma groups. The distant echo of this history of oppression has determined the permanent establishment of the ‘nomad camp’, which constitutes tangible evidence of urban segregation. The analysis will focus particularly on the issues of forgetting and the control of collective memory, as fundamental mechanisms of the process of Othering.